2022
DOI: 10.3390/app122010518
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Allogeneic Bone Plate and Guided Bone Regeneration Efficiency in Horizontally Deficient Maxillary Alveolar Ridges

Abstract: (1) Background: Bone Lamina Technique and Guided Bone Regeneration (GBR) are commonly used for horizontally-deficient maxillary ridge reconstruction, although more detailed evaluation to assess the differences between such techniques is necessitated. (2) Methods: In this retrospective study, patients having a horizontal bone width of ≤4 mm in the maxilla, who were treated with Cortical Strut (CS), were collected to represent the “test group”, and those treated with GBR with no CS involvement represented the “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Regarding buccal plate regeneration, the buccal bone plate of the alveolar process is a critical component closely related to the tooth it supports, and its remodeling can impair the cosmetic and functional success of implant surgery at the affected locations [18]. Various surgical techniques can replace alveolar bone loss, distraction osteogenesis, and inlay and on lay grafting, including GBR, free vascularized auto grafts, and ridge splitting [4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding buccal plate regeneration, the buccal bone plate of the alveolar process is a critical component closely related to the tooth it supports, and its remodeling can impair the cosmetic and functional success of implant surgery at the affected locations [18]. Various surgical techniques can replace alveolar bone loss, distraction osteogenesis, and inlay and on lay grafting, including GBR, free vascularized auto grafts, and ridge splitting [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hard tissue can be improved using the well-known GBR procedure, which can repair both horizontal and vertical flaws. Autogenous bone grafts are the gold standard for hard tissue augmentation treatments because they transmit vital minerals, proteins, and bone-related cells to the recipient location, encouraging bone regeneration and boosting bone augmentation success [2,4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Allografts can be used in either the particulate or block graft form and can be used alone or combined with autogenous, xenogeneic, or alloplastic materials. When evaluating and comparing GBR procedures with allogeneic and autologous bone grafts, several authors have reported comparable results and similar survival and success rates for implants placed in augmented areas [ 17 ].…”
Section: Introductionmentioning
confidence: 99%